Identification and Expression Profile of Olfactory Receptor Genes Based on Apriona germari (Hope) Antennal Transcriptome - Qian, Jia-Li; Mang, Ding-Ze; Lv, Guo-Chang; Ye, Jia; Li, Zhao-Qun; Chu, Bo; Sun, Long; Liu, Yu-Jun; Zhang, Long-Wa (Frontiers in Physiology, 2020)
Insect olfactory receptor plays a central role in the detecting chemosensory information from the environment. Odorant receptors (ORs) and ionotropic receptors (IRs) are two types of olfactory receptors, and they are essential for the recognition of ligands at peripheral neurons. Apriona germari (Hope) (Coleoptera: Cerambycidae) is one of the most serious insect pests that causes damage to economic trees and landscaping trees, resulting in massive environmental damages and economic losses. Olfactory-based management strategy has been suggested as a promising strategy to control this woodboring beetle. However, olfactory perception mechanism in A. germari is now almost unknown. In the present study, RNA sequencing analysis was used to determine the transcriptomes of adult A. germari antennae. Among 36,834 unigenes derived from the antennal assembly, we identified 42 AgerORs and 3 AgerIRs. Based on the tissue expression pattern analysis, 27 AgerORs displayed female-biased expression. Notably, AgerOR3, 5, 13, 33 and 40 showed a significant female-biased expression and were clustered with pheromone receptors of Megacyllene caryae in the phylogenetic tree, suggesting that these AgerORs could be potential pheromone receptors for sensing male-produced sex pheromones in A. germari. AgerIRs expression profile demonstrated that AgerIR2 had high expression levels in male labial palps, suggesting that this receptor may function to detect female-deposited trail-sex pheromone blend of A. germari. In addition, phylogenetic tree showed that Orco gene of five cerambycidae species were highly conservative. These results provide a foundation for further studies on the molecular mechanisms of olfactory chemoreception in A. germari apart from suggesting novel targets for control of this pest in the future.